THE INFLUENCE OF THE STUDY OF PHILOSOPHY ON THE QUALITY OF PROFESSIONAL TRAINING OF CADETS - Voloshina, N.; Hanhal, A. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2023)
The article analyzes different approaches of domestic and foreign authors to modern processes of humanitarianization of higher education and the role of philosophy in the training of specialists in the non-humanitarian sphere. A short excursion into the history of scientific views on the worldview content of philosophy and its role in the formation of a person’s worldview is made. It has been proven that it is philosophy that provides a person with self-knowledge, and human life with worldview orientations. It is rightly believed that true philosophy is the spiritual quintessence of the age, the living soul of science. It is substantiated that the task of holistic understanding from philosophical positions of both natural and social reality through the opposition of man and the world remains the most important even today, especially in connection with radical changes in all spheres of modern life and the need to clarify these changes. Attention is drawn to a specific pragmatic task - to arm the future specialist with general ideas about the problems and methods of philosophy, to teach him to find an answer for himself to the question: "How does this theoretical position relate to the realities of my future military service?". The possibilities of philosophy with the help of a system of universal principles, laws and categories about the relationship, development and knowledge of nature, thinking and society to understand the nature, essence and meaning of modern hybrid war are revealed. The role of philosophical categories as a kind of general scientific equivalent in understanding the complex interweaving of concepts and categories of different sciences, establishing the degree of similarity and difference between the concepts used in military science and the concepts of other sciences is determined.